A case study of graphic organizers effects on Chinese High School students critical thinking in EFL reading class - Min, Guo Si (2022)
Promoting students critical thinking (CT) is an increasing concern in China. This study investigated the effects of graphic organizers (GOs) on 60 Chinese senior high school students CT skills (analyzing and generalizing) in EFL reading classes. This study adopted mixed-methods research design. It collected data using a quasi-experimental approach and an interview. The findings of this study showed positive impacts of GOs on students CT skills. After the intervention, the experimental groups results improved significantly. There was also a significant difference in the reading performance test scores between the control and experimental group in the post-test. The findings showed that GOs can effectively improve the analytical and generalization skills of Chinese high school English reading class students. The students in the experimental group reported that the instructions received made them more aware of CT skills and they also learned how to apply GOs in the real reading contexts. The implication of this study is teachers may consider GOs as alternative teaching tools to improve CT skills in English Language reading classes.